The perception of corporate services in a Metropolitan Municipality on King III good governance compliance - Mutiro, Newton Sly (Cape Peninsula University of Technology, 2013)
Good governance has been and is a growing phenomenon for almost all business organisations regardless of size, profit margins and purpose for existence. Government, quasi-government, non-governmental organisations and even civic organisations have adopted a project-based approach to business. The City of Cape Town Metropolitan Municipality is one such organisation that had adopted a project-based approach to business. The challenge was how to effectively and efficiently implement governance issues around projects and business organisations. Most organisations can easily be misled if issues of governance are not clearly defined and followed. A project-based approach helps in defining the resources needed at specific times, the time required for a specific task and the cost of a specific operation. In a multi-project environment (programme) resources are shared in a well-defined manner. The City of Cape Town Metropolitan Municipality has a huge responsibility in terms of successfully initiating, planning and implementing projects successfully. The magnitude and the dynamic complexities of their operation call for proper governance structures to be established within any municipality if service delivery is the main objective. Managing complex and mega projects calls for certain leadership traits. A fusion of these traits at different management levels will be critical for effective delivery of services to the electorate. Models and plans need to be in place as guidance to successful implementation of projects. A number of people, committees and institutions have developed different governance frameworks that can be adopted by organisations as a guide to good governance. This research is based on King III guide to good governance. Challenges experienced by other Municipalities and business organisations e.g. Nelson Mandela Municipality, Eastern Cape Education Department, Transnet, LeisureNet, Limpopo Provincial government and many others, directly relate to poor governance. This therefore calls for the investigation of the Corporate Services directorate in the City of Cape Town Metropolitan Municipality to establish the level of compliance with what King III had recommended as a framework for good governance. The City of Cape Town Metropolitan Municipality has different general governance frameworks in place. However they do not use them effectively because of different issues identified by the researcher. The major challenges facing the City of Cape Town Metropolitan Municipality are effective governance communication and lack of training in the practice of good governance. There were serious discrepancies when it comes to understanding and interpreting governance issues within the different levels of management. It is expected that an organisation like the City of Cape Town Metropolitan Municipality should have proper communication channels and effective training programmes. The researcher also found that information is not readily available to people who need it most yet the expectation is that information be readily available.
Thesis submitted in partial fulfilment of the requirements for the degree Master of Technology: Business Administration in Project Management in the Faculty of Business at the Cape Peninsula University of Technology 2013
Keywords: Shared services (Management); Corporations, Government -- Shared services; Project managment -- South Africa; Economic development -- South Africa; MTech